Panencephalopathic type of Creutzfeldt-Jakob disease: primary involvement of the cerebral white matter - Mizutani, Toshio (1981)
Eight necropsy cases of a “panencephalopathic” type of Creutzfeldt-Jakob disease (CJD) in the Japanese are reported. The reasons why this type should be discussed separately from other types of CJD are that there is primary involvement of the cerebral white matter as well as the cerebral cortex, and that the white matter lesion of one Japanese human brain with CJD similar to the present group has been successfully transmitted to experimental animals.